Pigskin Treatment Using Different Food-Grade-Acids: Effects on The Physicochemical Characteristics of The By-Products - Velazquez, Diego Ezequiel (2023)
Upcycling foods contributes to reducing food loss and waste and provides sustainable solutions to novel products. In the present work, it was studied the use of food-grade acids (Acetic(AH), Latic(AL), Citric(AC), and Ascorbic(AA) acid) to obtain pigskin by-products, acid-soluble collagen (ASC), and gelatin (G). The aim was to evaluate the effect of the use of different food-grade acids on pigskin by-product characteristics. The physicochemical and thermal features, including Hydroxyproline (Hyp), pH, Differential Scanning Calorimetry (DSC), and color, were evaluated on by-products. The ASC and G solutions pH´s showed relation with the acid solution pH used. The AH and AA ASC fractions, showed lower Hyp content than AC and AL-treatments. By contrast, G Hyp-content was higher for AH and AA than AC and AL-treatments. The dried ASC-AH and -AA thermal transition temperatures (Td) resulted lower than AL and AC. The four dried-G samples showed an endothermic signal around 120 °C but with differences on enthalpy values. Current results suggest that the acid used and the pH of the solution during the thermal process would affect the physical-chemical properties of the by-products. The possibility to obtain different pigskin by-products using food grade acid could be an option for obtaining novel ASC and G use. Independently of the treatment, the G by-product was the main yield. Likewise, further studies are required to understand the by-products chemical differences and their potential uses.